Self-compassion dan rasa syukur dengan kesejahteraan psikologis dosen Perguruan Tinggi Negeri: Gaya kepemimpinan sebagai moderator: Self-compassion and gratitude with the psychological well-being of lecturers at State Universities: Leadership style as a moderator - Yudiani, Ema; Istiningtyas, Listya; Meyrinda, Jesyia; Khosiyah, Siti (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to examine self-compassion and gratitude with psychological well-being moderated by leadership style in lecturers at South Sumatra State Universities. The participants of this study were 452 lecturers, and the participants were taken using purposive sampling techniques. This research instrument uses the psychological well-being scale (Cronbach's alpha a = 0.852), the Multifactor Leadership Style MLQ-5X Scale (Cronbach's alpha a= 0.85.), and the Self-compassion Scale (Cronbach's alpha a = 0.817). The data were analyzed using Structural Equation Modeling (SEM). The results of the model test analysis using path analysis found that the role model of leadership style as a moderator variable of the influence of self-compassion and gratitude on psychological well-being in PTN lecturers is fit and significant. Furthermore, the results of moderated regression analysis found that leadership style provides a moderator role in self-compassion and gratitude on psychological well-being. This study highlights the moderating effect of leadership style on work climate, self-compassion, and gratitude on psychological well-being, which shows that the high or low influence of work climate, self-compassion, and gratitude on psychological well-being depends on the high or low moderation of leadership style.